Решить уравнение.   [latex] \frac{1}{4x + 8} = \frac{20x + 1}{4x^{2} - 16} - \frac{7 - 5x}{x^{2} -4x + 4}[/latex]

Решить уравнение.   [latex] \frac{1}{4x + 8} = \frac{20x + 1}{4x^{2} - 16} - \frac{7 - 5x}{x^{2} -4x + 4}[/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]\frac{1}{4x+8}=\frac{20x+1}{4x^{2}-16}-\frac{7-5x}{x^{2}-4x+4} \\ \\ x\neqб2 \\ \\ \frac{1}{4(x+2)}=\frac{20x+1}{4(x-2)(x+2)}-\frac{7-5x}{(x-2)^2} \\ \\ \frac{(x-2)^2}{4(x+2)(x-2)^2}= \frac{(20x+1)(x-2)}{4(x-2)^2(x+2)}-\frac{4(x+2)(7-5x)}{4(x+2)(x-2)^2} \\ \\ \frac{x^2-4x+4}{4(x+2)(x-2)^2}= \frac{20x^2-40x+x-2}{4(x-2)^2(x+2)}-\frac{(4x+8)(7-5x)}{4(x+2)(x-2)^2} \\ \\ \frac{x^2-4x+4}{4(x+2)(x-2)^2}= \frac{20x^2-39x-2}{4(x-2)^2(x+2)}-\frac{28x-20x^2+56-40x}{4(x+2)(x-2)^2}[/latex]   [latex]x^2-4x+4=20x^2-39x-2-(-12x-20x^2+56) \\ x^2-4x+4=20x^2-39x-2+12x+20x^2-56 \\ x^2-4x+4=40x^2-27x-58 \\ 39x^2-23x-62=0 \\ D=(-23)^2-4*39*(-62)=529+9672=10201=101^2 \\ \\ x_1=\frac{23+101}{2*39}=\frac{62}{39}\ \ \ \ \ \ \ \ x_1=\frac{23-101}{2*39}=-1[/latex]   Ответ: [latex]-1;\ \frac{62}{39}[/latex]
Гость
1 знаменатель: 4(х+2) 2 знаменатель: 4(х-2)(х+2) 3 знаменатель: (х-2)^2 общий знаменатель: 4(х+2)(х-2)^2 числитель: (х-2)^2 - (х-2)(20х+1) + 4(х+2)(7-5х) = 0 х^2-4x+4 - (20х^2-39х-2) + 4(7х-5х^2+14-10x) = 0 х^2 - 4x + 4 - 20х^2 + 39х + 2 + 28х - 20х^2 + 56 - 40x = 0 39х^2 - 23х - 62 = 0 D = 23*23 + 4*39*62 = 101*101 x1 = (23-101)/(2*39) = -78/78 = -1 x2 = (23+101)/(2*39) = 124/78 = 1_46/78 = 1_23/39  
Не нашли ответ?
Ответить на вопрос
Похожие вопросы